Building trust and fostering cooperation: How Malaysian LIS professionals sustain a Community of Practice on Facebook - A. Azizan,; A. Abrizah,; Samsuddin, Samsul Farid; Ali Fauzi, (Malaysian Journal of Library and Information Science, 2025)
Despite the ubiquity of social media in professional development, the mechanisms sustaining trust and cooperation within non-Western library communities remain underexplored. This study examines these dynamics within Sembang Pustakawan, a prominent Malaysian Facebook-based Community of Practice (CoP). Employing a mixed-methods approach, data were collected via a survey of 174 librarians and in-depth interviews with ten active members. The findings demonstrate that trust is established through demonstrated expertise, respectful communication, and the visible reliability of shared information. Cooperation is enacted through collaborative problem-solving and mentorship, effectively functioning as peer-led professional development. While social media affordances - visibility, persistence, association, and editability - facilitate these interactions, the study also reveals the fragility of online engagement, where participation is threatened by commercial interference and uneven contribution rates. Ultimately, this research extends affordance theory by illustrating how digital features intersect with culturally grounded professional solidarity to sustain a resilient, self-correcting network.